(untitled) (World Science, 2020)
The question of the changes in red blood cells metabolism markers based on the pathogenetic features the course of traumatic disease in polytrauma remains open and relevant. Objective of this study was to evaluate changes in the functional state of red blood cells during hypoxia in patients with traumatic disease. A prospective randomized controlled clinical trial was carried out on 120 patients on the basis of the Polytrauma department. The main markers of the functional state of red blood cells (lactate, pyruvate, 2.3-diphosphoglyceric acid, ATP) were determined by spectrophotometric method. We have revealed that the course of the acute and early periods of traumatic disease is accompanied by changes in the functional state of red blood cells. This is evidenced by a decrease in ATP level and an increase in the levels of lactate, 2,3-DFH and lactate/pyruvate index. We have established a relationship between the markers of the functional state of red blood cells at the time of admission and the development of infectious complications, posthemorrhagic anemia, posttraumatic nephropathy.